Analysis of the Solid Electrolyte Interphase on Hard Carbon Electrodes in Sodium‐Ion Batteries. Issue 6 (7th February 2019) - Carboni, Marco; Manzi, Jessica; Armstrong, Antony Robert; Billaud, Juliette; Brutti, Sergio; Younesi, Reza
Abstract: The composition, morphology, and evolution of the solid electrolyte interphase (SEI) formed on hard carbon (HC) electrodes upon cycling in sodium‐ion batteries are investigated. A microporous HC was prepared by pyrolysis of d ‐(+)‐glucose at 1000 °C followed by ball‐milling. HC electrodes were galvanostatically cycled at room temperature in sodium‐ion half‐cells using an aprotic electrolyte of 1 m sodium bis(trifluoromethanesulfonyl)imide dissolved in propylene carbonate with 3 wt % fluoroethylene carbonate additive. The evolution of the electrode/electrolyte interface was studied by impedance spectroscopy upon cycling and ex situ by spectroscopy and microscopy. The irreversible capacity displayed by the HC electrodes in the first galvanostatic cycle is probably due to the accumulation of redox inactive Nax C phases and the precipitation of a porous, organic‐inorganic hybrid SEI layer over the HC electrodes. This passivation film further evolves in morphology and composition upon cycling and stabilizes after approximately ten galvanostatic cycles at low current rates. Abstract : Round in cycles : The irreversible capacity losses in hard‐carbon negative electrodes for Na‐ion batteries originates from the irreversible trapping of Na + in Nax C compounds and the precipitation of a porous, organic‐inorganic hybrid solid electrolyte interphase. This surface layer mainly contains Na2 CO3 and NaF, precipitates in the first galvanostatic cycle, and further evolves in morphology and composition in the following cycles.